Web-Based Student Activity Credit Unit Information System at State Polytechnic of Banyuwangi - Agus Priyo Utomo; Junaidi Adi Prasetyo; Devis Alfian Rhamadhani; Mohamad Dimyati Ayatullah (Jurnal Jaringan Telekomunikasi, 2023)
The student Activity Credit Unit is a credit value obtained by students after participating in curricular and extracurricular student activities. The credit score is a specific value unit in the form of numbers given to each student who carries out actions. Credit score provisions have been set. Each activity must be accompanied by proof of participation/certificate/other evidence that will be used as the basis for assessing creditworthiness. If the calculation of the loan amount is done manually, errors can occur because the work done by humans is relatively error prone. Therefore, we need an application that provides a solution to minimize the occurrence of computational errors. This research was conducted to create a credit unit information system for student activities using the PHP programming language with the Laravel framework and MySQL as the database. This system makes it easier for students to input data on student activities. The result of this research is a web-based credit information system for student activities that can be implemented at the State Polytechnic of Banyuwangi as a tool for calculating credits for all student activities.